THE POTENTIAL OF HIDDEN OBJECT GAMES TO ASSIST ENGLISH VOCABULARY ACQUISITION FOR ESL LEARNERS: A COMPREHENSIVE VIEW - Hendrik Yohant Possumah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This article explores the potential of using Hidden Object (Video) Games as a media to enhance students experience in learning English vocabulary among ESL learners. The role of vocabulary in ESL is essential and critical, and effective vocabulary acquisition is key in improving language proficiency. Hidden Object Games (HOGs), popular for their engaging and immersive gameplay, offer a different and unique opportunity to integrate challenging yet fun activity in vocabulary learning. Moreover, HOGs enhance students experience by providing immerse and context-rich environment that promotes repeated exposure to new vocabularies in meaningful contexts, hence complimenting retention and application. This paper will discuss the benefits of these games, such as increased engagement, as well as challenges like technological barriers. Finally, several suggestions on how HOGs can assist teachers in vocabulary learning will also be discussed. It is my contention that HOGs, when carefully planned and implemented alongside traditional instructional methods, can become an amazing ally to help teachers in improving class experience and ESL vocabulary instruction, offering an interactive and immersive platform for vocabulary acquisition.